Hello,
Factorize above by 1+a and below by b.
As you have noticed, bc=(1+a)(1-a)
Hence
->
Is it clear ? :-)
If (a^2) + bc = 1 (a, b, c are given real numbers) , show that
(cx - y(1+a))/(by - x(1-a)) = -(1+a)/b = -c/(1-a).
where (x and y are any real numbers)
I thought factoring: bc = 1 - (a^2) = (a+1)(a-1).
From this it is easily shown that -(1+a)/b = -c/(1-a).
But how to show that any of these equals: (cx - y(1+a))/(by - x(1-a)).
It all seems quite intriguing to me. Does anyone see any light here?